Perencanaan Ekstrakurikuler Kerohanian Islam (Rohis) Di Madrasah Aliyah Al-Fatah Palembang - Zulkipli; Hidayat; Ibrahim; Praja, Ade (Fitrah: Journal of Islamic Education, 2020)
This study aims to analyze: (1) Rohis extracurricular planning. (2) Supporting and inhibiting factors of Rohis Extracurricular planning in MA Al-Fatah Palembang. The research method used is qualitative research methods based on descriptive studies. The results of the study concluded that Rohis extracurricular planning at MA Al-Fatah Palembang had gone according to a predetermined plan, the indicators could be seen from: (1) setting goals or targets on the Rohis extracurricular activities, in this case the aim was for students to better understand Islamic teachings, have noble character, good manners, both towards parents, and with teachers. (2) Creating an action strategy, it can be seen that many achievements given by Rohis members to madrasah mean that the Rohis extracurricular strategy has reached the stage of success. (3) Arranging a series of Programs, such as Rohis extracurricular activities, has implemented a schedule of daily, weekly, monthly and yearly activities. The supporting factors are having an organized training program, having a coach who is an expert in his field, and support from the madrasa. While the inhibiting factor is the lack of student interest, the limited duration of training time, facilities that are less supportive.